AJARAN AHIMSA DALAM BHAGAVADGĪTĂ - I Made Gami Sandi Untara; Ni Made Supastri (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Bhagavadgȋtā is a very important holy book which gives a deep spiritual understanding of life. The Bhagavadgȋtā text is divided into 700 sloka which are summarized in 18 chapters or adhyaya. In addition to learning what the Almighty God means, the Bhagavadgȋtās, living beings, the Bhagavadgȋtā also learns about the teachings of Ahimsa. Ahimsa teachings emphasize not killing, not hurting and without violence. Ahimsa as a teaching that does not do violence. It is true that killing is a form of violence. But there are murders which are permitted and even required by Vedic teachings. Killing to preserve life is not an act of Himsa karma. Even the Bhagavadgȋtā which is conveyed by the Personality of Godhead, Sri Krishna is an order for Arjuna to rise and do his duty to kill his opponents on the battlefield. Murder must be carried out in order to perform duties and obligations.